Web content accessibility and its relation to Webometrics ranking and search engines optimization - Elgharabawy, Mohamed Ahmed; Ayu, Media Anugerah (2011)
Educational institutes compete to achieve higher ranking in different world ranking systems. This is because higher ranking gives the institute more recognition worldwide. Webometrics is one of the most famous ranking systems for high learning institutions. The study tries to investigate the relation between Webometrics ranking and WCAG conformance. Does WCAG conformance affect Webometrics? Is this effect significant? The study also investigates the relation between WCAG conformance and search engines ranking. The aim of this study is to find out whether accessibility can be used as a tool for search engines optimization or not. Results indicate that there is a positive relation between Webometrics and WCAG conformance. Though the results showed a weak correlation between measured variables, the trend was always positive. As for WCAG conformance and search engines ranking, results showed a weak positive trend almost in all cases which indicates that accessibility could be recommended as a tool for search engines optimization.